The patriot poets : American odes, progress poems, and the state of the union - Adams, Stephen, 1945- (McGill-Queen's University Press, 2018)
"Since before the Declaration of Independence, poets have shaped a collective imagination of nationhood at critical points in American history. In The Patriot Poets Stephen Adams considers major odes and "progress poems" that address America's destiny in the face of slavery, the Civil War, imperialist expansion, immigration, repeated financial boom and bust, gross social inequality, racial and gendered oppression, and the rise of the present-day corporate oligarchy. Adams elucidates how poets in the nineteenth and twentieth centuries have addressed political crises from a position of patriotic idealism and how military interventions overseas in Cuba and in the Philippines increasingly caused poets to question the actions of those in power. He traces competing loyalties through major works of writers at both extremes of the political spectrum, from the radical Republican versus Confederate voices of the Civil War, through New Deal liberalism versus the lost-cause propaganda of the defeated South and the conservative isolationism of the 1930s, and after the Second World War, the renewed hope of Black leaders against the existential alienation of Allen Ginsberg's counter-culture. Blazing a new path of critical discourse, Adams questions why America, of all nations, has appeared to rule out politics as a subject fit for poetry. His answer draws connections between familiar touchstones of American poetry and significant yet neglected writing by Philip Freneau, Henry Timrod, Sidney Lanier, William Vaughn Moody, Archibald MacLeish, Allen Tate, Genevieve Taggard, Muriel Rukeyser, Melvin B. Tolson, and others. An illuminating and pioneering work, The Patriot Poets provides a rich understanding of the ambivalent relationship American poets and poems have had with nation, genre, and the public."--